Family-Friendly Work Practices and Job Satisfaction and Organizational Performance: Moderating Effects of Managerial Support and Performance-Oriented Management. (December 2013) - Ko, Jaekwon; Hur, SeungUk; Smith-Walter, Aaron
Management literature has emphasized the influence of family-friendly work practices (FFWPs) on work attitudes and organizational performance because there has been an increase in the number of women and dual-career couples in the workforce. However, previous studies on FFWPs yielded inconclusive results and focused on the direct relationship between FFWPs and outcomes. This study explores the influence of FFWPs on job satisfaction and organizational performance. Also, we investigate the moderating effects of managerial support and performance-oriented management. Results support the moderating effect of managerial support. But, findings regarding the moderating role of performance-oriented management do not support our expectation.